A rare case of congenital epidermoid cyst of the hard palate. (24th October 2011) - Montebugnoli, Lucio; Tiberio, Cristiana; Venturi, Mattia
Abstract : Epidermoid cysts are benign conditions that are thought to derive from abnormally situated ectodermal inclusions in the oral cavity. They are generally found in hands, fingers, feet, ovaries and testicles but in oral cavity they represent a very rare event. This is the first case of an intraosseous epidermoid cyst situated in the hard palate. Healing was uneventful and there was no sign of recurrence in 2-years follow-up.